2019
DOI: 10.1002/elan.201900053
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characteristics of a Triphenylamine Derivative by Microelectrode Voltammetry

Abstract: With the objective of understanding the kinetic redox properties of triphenylamine derivatives in association with chemical reactions, for their future application in functional organic semiconductor devices, the electrochemical characteristics of 4‐(2,2‐diphenylethenyl)‐N,N‐bis(4‐methylphenyl)‐benzenamine (TPA) were evaluated. Based on cyclic voltammograms of TPA on Pt disk electrodes with diameters of 300 μm and 10 μm at slow and fast scan rates in an acetonitrile solution, the TPA.+ is stable, while the TPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The first oxidation current is reversible, but the second one is irreversible. 11 In contrast, there is no reduction peak current at the negative potential region down to ¹1.2 V vs. Ag/AgCl. Hence, it was confirmed that TPA is a hole transport material.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first oxidation current is reversible, but the second one is irreversible. 11 In contrast, there is no reduction peak current at the negative potential region down to ¹1.2 V vs. Ag/AgCl. Hence, it was confirmed that TPA is a hole transport material.…”
Section: Resultsmentioning
confidence: 98%
“…In consequence, the E 1/2 for oxidation and IP HOMO are calculated to be 0.83 V vs. Ag/AgCl (1.03 V vs. SHE) and 5.53 eV, respectively, which correspond to the results of a previous report. 11 Therefore, the energy barrier height of hole injection into TPA on the Au electrode is estimated to be 0.43 eV because the work function for Au was reported as 5.1 eV. 14 In contrast, the barrier height for electron injection is assumed to be >1.6 eV since E 1/2 for reduction is <¹1.2 V vs. Ag/AgCl.…”
Section: Resultsmentioning
confidence: 99%
“…All the three polymers showed the irreversible oxidation at 0 to −1 V, while ACP‐Cz‐Bz (that contains only carbazole units) showed comparatively narrower oxidation, triphenyl amine containing polychalcone showed broad oxidation region. This could probably due to possible multiple oxidation of states of triphenylamine 48 concomitant with that of chalcones 49 and other similar systems 50 …”
Section: Resultsmentioning
confidence: 99%
“…A Pt disk with a diameter of 10 μm, a Pt plate, and a Ag/AgCl/saturated KCl were used as working, counter, and reference electrodes, respectively. The ϕ10 μm Pt electrode was prepared using the procedure described in a previous study 31 . Two types of electrolyte were used.…”
Section: Methodsmentioning
confidence: 99%
“…Triphenylamine derivative single crystals produced by the solution method 27 29 exhibit excellent conductive properties, and their hole-transport activation energy is equivalent to that of pentacene 30 and rubrene 21 single crystals. Furthermore, stable and energetically favorable hole transport has been achieved via the first oxidation state of triphenylamine derivative 31 . Therefore, triphenylamine derivatives are attracting attention for application to highly functional organic devices.…”
Section: Introductionmentioning
confidence: 99%